A hospitalidade e a oferta de serviços no turismo religioso: o caso do Santuário Nacional de Nossa Senhora Aparecida - ANTUNES, Ana Cláudia Guimarães (2017)
Hospitality has a strong bond with religion. From primordial times, travels for religious fervor and devotion reasons are present in humanity, regardless of sex, creed or social status. Religious tourism can be a significant opportunity for the development of tourism, since tourists with religions reveal themselves more devoted to tourist destinations than to visit places with other motivations. Over the years different interests have enabled the formation of tourism structures that would receive tourists and pilgrims, whether in shrines, historic churches or popular festivals. In religious practices, the principle of welcoming, of the well-being of the parties involved, contributes to the production of symbolic exchanges, negotiations of demands, hospitality ties. Given the growing and significant influx of religious tourism and the assumption of the importance of relations of hospitality and religion, it is justified the present study that seeks to investigate the competitive strategy of religious tourist destinations and the need to broaden the discussions on religious tourism, understood as a promising segment in the tourism sector and that has the problem of research: how hospitality actions and the offer of tourism services contribute to gain competitive advantage in a religious destination? From the problem, the general objective was defined: to understand the relationship between the tourist services offered and the hospitality actions promoted by the Santuário Nacional de Nossa Senhora Aparecida and its contributions to the visitor. It was also sought to identify the relevance of hospitality to Sanctuary managers and visitors; to analyze the relationships between hospitality in the services offered and the strategy of competitiveness of the Sanctuary; identify the main stakeholders of the Sanctuary and the social relations existing between them. Three hypotheses were tested: (H1) the hospitality actions promoted by the Sanctuary contribute to the increase in the number of visitors; (H2) the tourist services offered by the Sanctuary positively influence visitor satisfaction and (H3) there is a relationship of hospitality between the Sanctuary and its stakeholders. As a methodology, an exploratory and descriptive, qualitative and quantitative empirical research was chosen, adopting the single case study method as proposed by Yin (2015), using the Bardin (1977) categorization method to content analysis performed on the information collected in the field procedures. The collection of evidences was carried out in a bibliographical, documentary and by means of interviews and a questionnaire based on the Likert Scale. All three hypotheses were confirmed.